A Yoruba Orpheus: Carnaval de Orfeo by J. Milián (Minerva, 2017)
In the Latin American theatre, especially in Cuba and Brazil, with a high black population, Greek heroes of this race were represented on stage for the first time. Black Orpheus, created by the Brazilian Vinicius de Moraes in his dramatic work Orfeu da Conceição (1956), became worldwide popular thanks to the cinematographic version of Marcel Camus (Black Orpheus, 1959). This paper demonstrates the important influence of the works of this Brazilian author on the dramatic Carnaval de Orfeo (1980) by José Milián (from Cuba), and analyses an interesting cultural syncretism that occurs on stage, linking the known classical Greco-Roman myth with the Orishas of Yoruba mythology.
Keywords: greco-roman mythology; classical tradition; theatre; comparative literature; comparative mythology; black Orpheus